RANGE EXPANSION OF Sakesphorus canadensis loretoyacuensis (AVES: THAMNOPHILIDAE) TOWARDS THE YAGUAS RIVER, LORETO, PERU - GRANDEZ-CASADO, Joaquín Abel (2025)
Sakesphorus canadensis is a Thamnophilid antbird distributed along the major river systems of northern South America. In Peru, it is typically associated with blackwater habitats in the northern Amazon, particularly within the Loreto Department. Here, we report the first record of S. c. loretoyacuensis in the Yaguas River basin, Putumayo Province, near the border with Colombia. This finding represents the northernmost record of the species in Loreto, extending its known distribution by approximately 120 km northward. The presence of this species in the Yaguas basin underscores the importance of continued biodiversity surveys in remote regions to improve our understanding of the country's avifauna.